Evaluasi Kegiatan Pengajian Rutin Malam Jumat Sebagai Media untuk Meningkatkan Kerukunan, Toleransi dan Keberagamaan Masyarakat - Azwar Rahmat; Suhirman Suhirman (Indonesian Journal of Research in Islamic Studies, 2025)
Background: Routine community religious gatherings like weekly recitations enhance spiritual knowledge and social bonds, yet their effectiveness is rarely evaluated systematically at the grassroots level. Objective: This study aims to evaluate the routine Friday night recitation activities to improve the religious knowledge of the community in Timur Indah V, Bengkulu City. Method: This study uses an evaluation approach with the Formative-Sumative Evaluation Model, which focuses on formative evaluation to measure the process and outcomes of the pengajian (Islamic study) activities. Data were collected through observation, interviews, and documentation, while data analysis was conducted using triangulation techniques to ensure the validity of the findings. Result: The process of implementing the Friday night recitation routine has been running according to procedures, although there are still some aspects of the instrument that have not been applied optimally. Regarding activity results, the congregation felt that this recitation greatly increased their religious insight. Conclusion: The routine Friday night recitation in Timur Indah V has positively impacted the congregation's understanding and religious practices. Although this activity has been running according to procedures, some aspects still need to be improved to increase its effectiveness. Contribution: This study empirically evaluates the effectiveness of routine recitation as a medium for religious education in the community.